Serendipita indica mitigates drought-triggered oxidative burst in trifoliate orange by stimulating antioxidant defense systems - Wang, Yu; Cao, Jin-Li; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Wu, Qiang-Sheng (Frontiers in Plant Science, 2023)
Soil drought is detrimental to plant growth worldwide, particularly by triggering reactive oxygen species (ROS) burst. Serendipita indica (Si), a culturable root-associated endophytic fungus, can assist host plants in dealing with abiotic stresses; however, it is unknown whether and how Si impacts the drought tolerance of citrus plants. To unravel the effects and roles of of Si on drought-stressed plants, trifoliate orange (Poncirus trifoliata L. Raf.; a citrus rootstock) seedlings were inoculated with Si and exposed to soil drought, and growth, gas exchange, ROS levels, antioxidant defense systems, and expression of genes encoding antioxidant enzymes and fatty acid desaturases in leaves were measured. Soil drought suppressed plant biomass, whereas Si inoculation significantly increased plant biomass (10.29-22.47%) and shoot/root ratio (21.78-24.68%) under ample water and drought conditions, accompanied by improved net photosynthetic rate (105.71%), water use efficiency (115.29%), chlorophyll index (55.34%), and nitrogen balance index (63.84%) by Si inoculation under soil drought. Soil drought triggered an increase in leaf hydrogen peroxide and superoxide anion levels, while Si inoculation significantly reduced these ROS levels under soil drought, resulting in lower membrane lipid peroxidation with respect to malondialdehyde changes. Furthermore, Si-inoculated seedlings under soil drought had distinctly higher levels of ascorbate and glutathione, as well as catalase, peroxidase, and glutathione peroxidase activities, compared with no-Si-inoculated seedlings. Si inoculation increased the expression of leaf PtFAD2, PtFAD6, Pt9, Pt15, PtFe-SOD, PtCu/Zn-SOD, PtPOD, and PtCAT1 genes under both ample water and soil drought conditions. Overall, Si-inoculated trifoliate orange plants maintained a low oxidative burst in leaves under drought, which was associated with stimulation of antioxidant defense systems. Therefore, Si has great potential as a biostimulant in enhancing drought tolerance in plants, particularly citrus.